CARBON DIOXIDE FIXATION IN BACILLUS ANTHRACIS - Eastin, Jerry D. (1963)
Eastin, Jerry D. (U.S. Army Chemical Corps, Frederick, Md.) and Curtis B. Thorne. Carbon dioxide fixation in Bacillus anthracis J. Bacteriol. 85:410–417. 1963.—Virulent strains of Bacillus anthracis require a concentration of CO(2) greater than that of the normal atmosphere (air) for the production of capsular material (glutamyl polypeptide); avirulent strains may produce no polypeptide or may produce polypeptide in air. Fixation of C(14)O(2) by each of the three types tested resulted in labeling of aspartic acid, glycine, glutamic acid, succinic acid, and an unidentified organic acid. C(14) was detected in aspartic acid after less than 30 sec of exposure of cells to C(14)O(2). Subsequent flushing of the cells with C(12)O(2) displaced C(14) from aspartic acid but not from the other labeled intermediates. Aspartic acid appears to be closely associated with the primary CO(2)-fixation product, and the data suggest a fairly direct carbon pathway from CO(2) to aspartic acid (oxaloacetic acid) to glutamic acid to glutamyl polypeptide.